The exceptional life : 8 powerful steps to experiencing God's best for you - Arterburn, Stephen, 1953- (Bethany House, 2011)
"The book presents eight issues that hold people back such as guilt, shame, fear, anger, and isolation and helps readers give them, replacing them with positives such as hope, love, trust, forgiveness, connection and community"--Provided by publisher.